(untitled) (International Seven Journal of Multidisciplinary, 2023)
Telemedicine is a form of remote medical care that has been essential in the global crisis caused by the Covid-19 virus. Despite being a recent, current and emerging issue, the method of digital medical care was already being developed in Brazil, albeit with some restrictions and criticism from the medical community, specifically the Federal Council of Medicine. In this context, the work will be based on the problem of data protection on digital platforms, in the dynamics of telemedicine. The legislation surrounding these issues will also be explored, with a special focus on the General Data Protection Act and the constitutional right to health and human dignity.